Application of finishing system to multipurpose rack from Kelepayan species / Norhidayu Zakariya - Zakariya, Norhidayu (2014)
This study focused on application of finishing system to multipurpose rack from Kelempayan (Neolamarckia cadamba) species. The main objective for this study is to determine the finishing properties of Kelempayan by using different finishing system and to study the furniture design of multipurpose rack. Two finishing system has been used that was system A and system B. Test that was performed to determine the finishing properties are surface roughness test, tape adhesion test, pencil hardness test and household test. Twice of sanding, sealer and topcoat applied on finishing system B was found to be the better system. System B should be applied to furniture since all the testing results shows that system B was better than system A.